HUBUNGAN AGILITY DAN KEMAMPUAN VERTICAL JUMP PADA PEMAIN BASKET MADRASAH ALIYAH NEGERI 4 JAKARTA - Nabila Rubianti (2022)
Basketball is one of the most popular sports in the world from children to adults and can be played by both men and women. In the game of basketball, several components are needed, namely agility or agility and vertical jumps or vertical jumps to pass the opponent and score into the basketball hoop. After researchers made observations on the basketball team of Madrasah Aliyah Negeri 4 Jakarta, there were still problems, namely the lack of agility of players in bouncing the ball quickly past the obstacles of each opponent, lack of high jumping ability such as layups, under the ring, jump shot and controlling speed and changing dribble direction. to score. The main purpose of this study was to find out how closely the relationship between agility and vertical jump ability in basketball players at Madrasah Aliyah Negeri 4 Jakarta. The type of research design used by the author is a cross-sectional study with a sample that has been adjusted to the inclusion criteria and exclusion criteria. A sample of 30 (n = 30) beginner basketball players (mean: age = 15 - 17 years; height = 150 - 180 cm; weight = 50 - 80 kg) were willing to participate in this study. The parameters used to determine how closely the relationship between agility and vertical jump are the Agility T-Test and Vertical Jump Test. After doing the correlation test with the Pearson product-moment technique, the results of the Pearson correlation r = -0.676 are not in the same direction. From the results of this study, it can be concluded that there is a non-unidirectional relationship between agility and vertical jump ability of basketball players at Madrasah Aliyah Negeri 4 Jakarta with a strong degree of correlation.